The Evolution of the Jihad Doctrine: Can Modern Islamic Terrorism Be Justified in Terms of Classical Jihad? (Groundings Undergraduate, 2010)
The proponents of modern Islamic fundamentalism draw on elements of the Islamic religion as a justification for terrorist acts. An examination of the sources of Islamic law – the Qur’an, the Sunnah and the principal Islamic schools of thought – questions the similarities between modern terrorism and the classical jihad doctrine. A distinction is drawn between the offensive and defensive theories of jihad and these are then applied to the modern context in which Islamic terrorism is perpetrated.
Keywords: Jihad; Islam; Terrorism; Fundamentalism; Justification; Jihad Doctrine; Classical Islam